HIV/AIDS, hepatitis and sexually transmissible infections in Australia: annual report of trends in behaviour 2012 - de Wit, John; Holt, Martin; Hopwood, Max; Treloar, Carla (UNSW Sydney, 2011)
This report reviews behavioural data relevant to the transmission of human immunodeficiency virus (HIV), viral hepatitis and sexually transmissible infections (STIs) in Australia. It also examines behavioural data relevant to the social aspects of treatment and care of those who have been infected, including those who are living with acquired immune deficiency syndrome (AIDS).
Monograph 3/2011
Keywords: Viral hepatitis; Sexually transmissible infections; HIV; Behavioural surveillance